Sitting Bull, warrior of the Sioux - Fleischer, Jane.; Dodson, Bert (Mahwah, NJ : Troll, 1979)
A brief biography of the only Indian ever to be chief of all the Plains Sioux.
School Library Journal
4.2
3-6
Keywords: Sitting Bull, -- 1834?-1890 -- Juvenile literature; Dakota Indians -- Biography -- Juvenile literature; Indians of North America -- Biography -- Juvenile literature; Sitting Bull, -- 1834?-1890.; Dakota Indians -- Biography; Indians of North America -- Biography; Sitting Bull, -- 1834?-1890.; Dakota Indians -- Biography; Native Americans -- North Dakota -- Biography